MIR-378 INDUCES APOPTSIS OF GRANULOSA CELLS DURING FOLLICLE DEVELOPMENT IN CATTLE - T. H. Ma; L. Cheng; B. Wang; Y. X. Shi; G. H. Liu; D. M. Lin1and B. Liu (Journal of Animal and Plant Sciences, 2017)
MicroRNAs (miRNAs) are small endogenous molecules that are involved in diverse cellular processes. However, little is known about the function of miRNAs in bovine ovary development. Previous study in our lab indicated miR-378 is an apoptosis-associated miRNA that participates in the regulation of bovine corpus luteum development. In addition, whether miR-378 regulates the apoptosis of bovine granulosa cells (bGCs) remains undetermined. Accordingly, this study evaluated the expression of miR-378 in granulosa cells (GCs) of dominant and subordinate follicles and analyzed the apoptosis rates of miR-378 mimics and mimics NC-transfected GCs by flow cytometry method. Results revealed that miR-378 was significantly expressed in the subordinate follicles compared with the dominant follicles, and the apoptosis rate and cleaved caspase-3, a hallmark of apoptosis, increased in the miR-378 mimics-transfected GCs in vitro. This study is the first to report that apoptotic miR-378 plays a regulatory role in bGCs, which will help to find a new way in the research of follicular atresia.
Keywords: miR-378; cattle; granulosa cell; follicle; ovary